Influence of inherent parameter of stabilized UHF oscillators on autodyne response formation at a strong reflected signal - Noskov V. Ya.; Ignatkov K. A.; Smolskiy S. M. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2011)
Results of an autodyne response analysis in UHF oscillators stabilized by the external high-Q cavity in the case of the strong signal when the reflected wave amplitude commen-surable with the own oscillation amplitude. Coupling between the basic operation cavity and the stabilizing cavity is implemented as a pass-reflecting filter with a resistive bond. Key relations are obtained, which describe the autodyne response to the own re-reflected radiation from a target. The load and oscillating system influence on autodyne response formation is fulfilled.